Going Native: Effects of Disclosure Position and Language on the Recognition and Evaluation of Online Native Advertising. Issue 2 (2nd April 2016) - Wojdynski, Bartosz W.; Evans, Nathaniel J.
Abstract : Despite recent industry attention, questions remain about how native advertising is perceived and processed by consumers. Two experiments examined effects of language and positioning in native advertising disclosures on recognition of the content as advertising, effects of recognition on brand and publisher evaluations, and whether disclosure position affects visual attention. Findings show that middle or bottom positioning and wording using "advertising" or "sponsored" increased advertising recognition compared to other conditions, and ad recognition generally led to more negative evaluations. Visual attention mediated the relationship between disclosure position and advertising recognition. Theoretical, practical, and regulatory implications for disclosures in native advertising are discussed.